Variation on water quality of Kerangas forest streams due to invasion of Acacia - Mohamad Hilmi, Ibrahim; Salwana, Jaafar (Springer Nature, 2025)
Acacia invasion has shown a negative impact on the water resources of forest streams. Therefore, studies need to be conducted demonstrating the importance of managing invasive species to preserve stream and forest ecosystems. This study investigates the effects of Acacia invasion on the water quality of Kerangas forest streams in Brunei. Water samples were collected from an Acacia-invaded (IN) stream and a non-invaded (NIN) stream during the dry season at three locations along each stream. Water properties, including pH, conductivity, salinity, total dissolved solids (TDS), phosphate, nitrate, ammonia, and nitrite, were analyzed using in situ and laboratory methods. The results showed that Acacia invasion significantly increased pH (from 4.01 to 5.68), nitrate (by 256%), and phosphate (by 250%) levels, while reducing conductivity (by 208%) and salinity (by 20%) compared to non-invaded streams. These findings suggest that Acacia invasion alters water chemistry, potentially posing risks to aquatic ecosystems. Effective management strategies, such as controlling Acacia spread and restoring native vegetation, are essential to mitigate these impacts and preserve forest water resources.